2021
DOI: 10.1126/sciadv.abd6889
|View full text |Cite
|
Sign up to set email alerts
|

BBB pathophysiology–independent delivery of siRNA in traumatic brain injury

Abstract: Small interfering RNA (siRNA)–based therapeutics can mitigate the long-term sequelae of traumatic brain injury (TBI) but suffer from poor permeability across the blood-brain barrier (BBB). One approach to overcoming this challenge involves treatment administration while BBB is transiently breached after injury. However, it offers a limited window for therapeutic intervention and is applicable to only a subset of injuries with substantially breached BBB. We report a nanoparticle platform for BBB pathophysiology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 57 publications
(93 reference statements)
1
68
0
Order By: Relevance
“…Evans blue (EB) staining shows high influx of dye with visible hematoma 1 day after TBI ( Fig. 5, D and E ), suggesting increased blood-brain barrier (BBB) permeability caused by TBI ( 44 ). Thus, O-NZ can rapidly penetrate across the damaged BBB and be trapped in the injured region for a long time to play the therapeutic role (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evans blue (EB) staining shows high influx of dye with visible hematoma 1 day after TBI ( Fig. 5, D and E ), suggesting increased blood-brain barrier (BBB) permeability caused by TBI ( 44 ). Thus, O-NZ can rapidly penetrate across the damaged BBB and be trapped in the injured region for a long time to play the therapeutic role (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus they never reach the CNS in significant amounts to have a biological outcome, and this may lead to poor efficacy in a clinical setting. Some examples exist for the entry of free siRNA (Xie et al, 2020) or siRNAencapsulated nanoparticles (Li et al, 2021) to enter the CNS, however, to date these intriguing approaches are only described to exert their therapeutic effect after a prior breach of the BBB and do not directly show transcytosis of the intact BBB. For example, some studies on traumatic brain injury indicate that BBB may be breached for several days after induction of trauma (Li et al, 2021), others indicate the BBB is permeable for weeks after initial injury (e.g., ischemia, blunt force trauma) (Strbian et al, 2008;Price et al, 2016), and some BBB tight junction components can be downregulated for up to 8 weeks (Nag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples exist for the entry of free siRNA (Xie et al, 2020) or siRNAencapsulated nanoparticles (Li et al, 2021) to enter the CNS, however, to date these intriguing approaches are only described to exert their therapeutic effect after a prior breach of the BBB and do not directly show transcytosis of the intact BBB. For example, some studies on traumatic brain injury indicate that BBB may be breached for several days after induction of trauma (Li et al, 2021), others indicate the BBB is permeable for weeks after initial injury (e.g., ischemia, blunt force trauma) (Strbian et al, 2008;Price et al, 2016), and some BBB tight junction components can be downregulated for up to 8 weeks (Nag et al, 2007). In addition, observation of brain penetration in Alzheimer's disease and Multiple Sclerosis models have shown a prior breach in the BBB as part of the pathogenesis of the disease (Ujiie et al, 2003;Bennett et al, 2010;Biron et al, 2011;Biron et al, 2013), and siRNA studies in these models similarly cannot be used to conclude transcytosis of siRNA across an intact BBB (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An issue with this method to deliver drugs using TBI BBB pathophysiology is the heterogeneity of the condition, the scale of the damage, and that the time to endogenous BBB repair is variable between patients. Rather than use the BBB damage to deliver the nanoparticles, a recent study in a TBI mouse model found success in delivering Tau-siRNA using nanoparticles coated with polysorbate 80 (PS 80) via the lipoprotein receptor [ 34 ]. Although not yet tested in humans, this therapy seems promising for the delivery of therapeutics across the BBB in patients with TBI.…”
Section: Methods To Combat Structural Chemical and Transport-mediated Challenges Of Drug Delivery Across The Bbbmentioning
confidence: 99%